Women, education, and agency, 1600-2000 [ - Aiston, Sarah Jane; Meikle, Maureen M.; Spence, Jean (Routledge research in gender and history, 2009)
A collection of essays that discusses topics that range from the strategies adopted by individual women to achieve a personal education and the influence of educated women upon their social